Evaluation of the Use of Dried Grated Sago as a Substitute Energy Source for Corn in Sentul Chicken Feed - Gunawan, Rinie (Unpad Press, 2024)
This research aims to evaluate dry grated sago as an energy source feed ingredient that can substitute corn in feed for the growth of Sentul chickens. The variables observed were feed consumption, final body weight, body weight gain, and feed conversion during growth from week 1 to week 10. The experimental design carried out was a completely randomized design with 5 treatments, namely corn-based feed (P0), feed sagoo more based feed without steam with the addition of 0.5% biopremix (P1), sagoo more based feed with steam adding 0.5% biopremix (P2), sagoo more based feed without steam with the addition of 1% biopremix (P3), and feed based sagoo more with steam adding 1% biopremix (P4). Each treatment consisted of 3 repetitions with 5 chickens per repetition. The total number of Sentul chickens used for the experiment was 150 chickens. The results of the research showed that the treatment feed was significantly different in terms of the average final body weight, body weight gain (PBB), and feed conversion (p<0.05) compared to the control, but the treatment feed was not significantly different in influencing feed consumption. The addition of 1% biopremix to rations without steam can increase the final body weight of Sentul chickens, increase body weight and reduce feed conversion compared to those with steam. Using Biopremix is more effective without steam treatment